A versatile bait vector allowing rapid isolation of prey vectors in Gal4-dependent yeast two-hybrid screens - Bannasch, Detlev; Schwab, Manfred (Plasmid, 2002)
Two-hybrid screens have been widely used in recent years for identifying and isolating new interaction partners to known proteins. Current Gal4-dependent two-hybrid screens employ mostly bait and library vectors, which both have the ampicillin gene as a selection marker in bacteria. The isolation of the library plasmids takes several days, because library and bait plasmid cannot be separated easily. We have replaced the ampicillin gene by a kanamycin gene in a Gal4 DNA binding domain bait vector. This vector reduces four- to fivefold the time period required for the isolation of library plasmid DNA. In addition we have changed the multicloning site in the modified vector for easy cloning of cDNA inserts. This vector is advantageous not only in standard two-hybrid screens, but also in mass screens that require multiple screening rounds in order to characterize networks of protein-protein interactions.